Teori modal insan untuk pembangunan profil pekerjaan bagi pelajar masalah pembelajaran dalam industri perkhidmatan makanan - Nik Norlaili Jamilah Nik Othman; Mohamad Sattar Rasul; Fathiyah Mohd Kamaruzaman (Penerbit Universiti Kebangsaan Malaysia, 2025)
The food service industry provides employment opportunities that can help students with learning difficulties develop work skills and contribute to the national economy, in line with the Sustainable Development Goals (SDGs). Various government incentives and the National TVET Policy 2030 support inclusive education and vocational skills. An approach based on Human Capital Theory is needed to develop suitable job profiles, enhancing workforce productivity and competitiveness. This study employs a comparative article analysis method based on the models used in the research. Articles were sourced from the Scopus database. The outcome of this model comparison will contribute to the development of job profiles based on categories of students with learning difficulties as a source of skilled and semi-skilled labor for the food and beverage service industry.